Does the Community Reinvestment Act Improve consumers' access to credit? - Jacob Conway; Jack N. Glaser; Matthew C. Plosser (Federal Reserve Bank of New York, 2023)
We study the impact of the Community Reinvestment Act (CRA) on access to consumer credit since 1999 using an individual-level panel and three distinct identification strategies: a regression discontinuity design centered on a CRA-eligibility cutoff; a comparison of neighboring census blocks; and an event study of changes in eligibility. All three rule out a significant effect of the CRA on consumer borrowing. We show that this is in part explained by a shift in mortgages from nonbanks, which are free from CRA obligations, to banks in need of CRA-eligible mortgages. Our findings underscore the pitfalls of a circumscribed regulatory regime.
Keywords: G21; G28; 330; Community Reinvestment Act; household finance; banks